Annual Plan 2003-2004 West Bengal Development and Planning Department Government of West Bengal - Planning Commission (Planning Commission, 2003)
There have been very remarkable achievements in the production of foodgrains in the State of West Bengal. The major breakthrough has come after introduction of High Yielding Varieties and implementation of various intensive crop development schemes consisting of State Plan, Central Sector and Centrally Sponsored Schemes. During Eighth Plan 130.82 (average of five years) lakh tonnes of foodgrains were achieved. In the terminal year of Ninth Plan (2001-2002), the State achieved foodgrain production to the tune of 165.01 lakh tonnes. Keeping the experiences in view, the State Govt, during formulation of Tenth Plan document has fixed an achievable target of 175.2730 lakh tonnes to attain self-sufficiency by the terminal year of Tenth Plan (2006-2007) to meet the demand of the growing population. The target of foodgrain production during 2002-2003 (1st year of Tenth Plan) has been fixed for 155 lakh tonnes.
Annual Plan 2003-2004 West Bengal
Government of West Bengal